Diabetic foot with risk for ulceration associated with diabetic retinopathy in type 2 diabetes - Irfan Ahmeti; Nevena Laban Guceva; Biljana Jovanovska; Tatjana Milenkovic; Katerina Adamova (European Society of Endocrinology, 2011)
Aim: To define impact of diabetic retinopathy as a risk factor at peoples with type 2 diabetes and diabetic foot. Material and methods: One hundred hospitalized patients with type 2 diabetes, screened for diabetic foot and diabetic retinopathy for 1 year. Clinical examination and laboratory investigations were evaluated. Results: From 100 patients, 53% were female and 47% male, duration of diabetes 10.47±4.77 years. Mean HbA1c was 8%±1.2%. HbA1c<7% had 18%, HbA1c 7–8% had 43% and HbA1c >8% had 49% of patients. At visit 1, risk score for diabetic foot ulceration is: low risk (0) 29%, medium risk (1) 35%, high risk (2) 18% and very high risk (3) 18%). Retinopathy was present with 68% – 53% non prolypherative and 15% prolypherative. According the risk score at visit 1 retinopathy had: in score 0 – 15% non-prolipherative and 0% prolipherative, score 1 – 18% non-prolypherative and 1% prolypherative, score 2 – 11% non-prolypherative and 6% prolypherative, and score 3 – 9% non-prolypherative and 8% prolypherative. After 12 months risk score for diabetic foot was: 0 – 17%; 1 – 39%; 2 – 19% and 3 – 27%. Diabetic retinopathy was present after 12 months 72% of which 51% non-prolypherative and 21% prolypherative. According the risk score after 1 year diabetic retinopathy were present: in score 0 – 6% non-prolyherative and 0% prolypherative, score 1 – 22% non-prolypherative and 3% prolypherative, score 2 – 10% non-prolypherative and 7% prolypherative, and score 3 – 13% non-prolypherative and 11% prolypherative. Conclusion: Association between risk score for foot ulceration and diabetic retinopathy was present. Group with risk score 0 and 1 have more non-prolypherative retinopathy and group with score 2 and 3 have more prolypherative retinopathy (Cross tabulation. Kruskal Wallis test P<0.01).
Keywords: diabetic foot; score; diabetic retinopathy.